5-(4-Fluorophenyl)-3-methylsulfanyl-2-phenyl-1-benzofuran - Choi, Hong Dae (International Union of Crystallography, 2011)
In the title compound, C(21)H(15)FOS, the dihedral angle between the mean plane of the benzofuran fragment and the mean planes of the pendant 4-fluorobenzene and phenyl rings are 31.72 (6)° and 32.51 (6)°, respectively. In the crystal, the molecules are linked by weak C—H⋯π interactions. The crystal studied was a merohedral twin with a 0.62 (9):0.38 (9) domain ratio.